Variability management with feature-oriented programming and aspects. - Mezini, Mira (Software engineering notes.)
This paper presents an analysis of feature-oriented and aspect-oriented modularization approaches with respect to variability management as needed in the context of system families. This analysis serves two purposes. On the one hand, our analysis of the weaknesses of feature-oriented approaches (FOAs for short) emphasizes the importance of crosscutting modularity as supported by the aspect-oriented concepts of pointcut and advice. On the other hand, by pointing out some of AspectJ's weaknesses and by demonstrating how Caesar, a language which combines concepts from both AspectJ and FOAs, is more effective in this context, we also demonstrate the power of appropriate support for layer modules.